Pengaruh Metode Information Serch Terhadap Hasil Belajar Akidah Akhlak Siswa Kelas Xi Man 2 Kota Payakumbuh - Dwi Gustina Affah; Wedra Aprison; Arifmiboy Arifmiboy; Iswantir Iswantir (Jurnal Riset Sosial Humaniora dan Pendidikan, 2023)
The background of this research is the low student learning outcomes of aqidah akhlah, because educators still use methods that make students bored and unenthusiastic in participating in learning, such as still using lecture, question and answer and assignment methods. So that there are still students who have less motivation in learning, as evidenced by the lack of students who are active in class, such as actively asking, answering and being active in expressing opinions, so that many students have not achieved predetermined learning outcomes. This study aims to describe: (1) Application of Information Search Methods for Class XI Man 2 Payakumbuh City, (2) Learning Outcomes of Aqidah Akhlak Class XI Man 2 Students in Payakumbuh City, (3) Effect of Information Search Methods on Learning Outcomes of Aqidah Akhlak Class XI Students Man 2 Payakumbuh City. This study uses a quantitative approach with a korean type. The population in this study was students of class XI Man 2 Payakumbuh City with a total of 137 students. The data collection technique is in the form of a questionnaire in the analysis using the r product moment formula, the correlation coefficient, and the coefficient of determination. But before the data is tested, the research is first tested using the normality test, linearity, and homogeneity test. Sampling using simple random sampling technique, by taking 25% of the population of 137 students. And the sample in this study were 34 students. The results of the Research Information Search Method for class XI students are in the high category with a percentage of 53%. While the results of research on the influence of information seeking methods on student learning outcomes of aqidah morals obtained results of 0.562. The results of the determination test were (0.5622) ï‚´ 100 ï€¥ = 31.58%. Then the perception of students' learning outcomes of aqeedah morals is 31.58% influenced by the application of information seeking methods, the remaining 68.42% is influenced by other factors not examined in this study. There is a significant influence between the Information Search Method and the learning outcomes of class XI student morals based on the coefficient of determination, the figure is 31.58%.